Image of Tripurantaka Shiva - Temples of India Project Team (Jio Institute, 2024)
The south-facing bhadra (central projection) of the Mahanlashwar Temple has an image of Tripurantaka Shiva. The left foot of the deity is uplifted to crush the demon. Among attributes, the deity is shown holding a raised trishula (trident), kapala (skull), sword and snake. This depiction of Tripurantaka is complimented with Natesha and Chamunda in the other two bhadras of the temple, indicating the Shaiva affiliation of the temple.